2020
DOI: 10.3390/s20030778
|View full text |Cite
|
Sign up to set email alerts
|

Feature Selection for Machine Learning Based Step Length Estimation Algorithms

Abstract: An accurate step length estimation can provide valuable information to different applications such as indoor positioning systems or it can be helpful when analyzing the gait of a user, which can then be used to detect various gait impairments that lead to a reduced step length (caused by e.g., Parkinson’s disease or multiple sclerosis). In this paper, we focus on the estimation of the step length using machine learning techniques that could be used in an indoor positioning system. Previous step length algorith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The experiment results implied that the camerabased method was a promising way to detect all steps when the user was moving slowly, especially in an indoor environment. Recently, the researchers in [21] proposed a machinelearning-based step length estimation algorithm with the use of cameras and smartphones. This research considered a systematic feature selection algorithm to determine the choice of user-specific parameters from a large collection.…”
Section: Related Workmentioning
confidence: 99%
“…The experiment results implied that the camerabased method was a promising way to detect all steps when the user was moving slowly, especially in an indoor environment. Recently, the researchers in [21] proposed a machinelearning-based step length estimation algorithm with the use of cameras and smartphones. This research considered a systematic feature selection algorithm to determine the choice of user-specific parameters from a large collection.…”
Section: Related Workmentioning
confidence: 99%
“…The dense layer branch input was built with a feature vector extracted from step/stride time series. Features comprise the mean, variance, root mean square (RMS), range, the sum of all values, the step time in seconds and foot size in centimetres (divided by a constant 30) [32,33]. The foot size was estimated from the sensing walkway data and used as a proxy for the participant's height since this latter demographic variable was not recorded in the study.…”
Section: Step/stride Length Dnn Modelmentioning
confidence: 99%
“…Song et al demonstrated the advantages of parameterized blackbox modeling over traditional human gait models with an ANN-based approach to predict walking or running speed over a large range of speeds [4]. Vandermeeren et al extracted a variety of different features to predict stride length from a smartphone accelerometer using multiple machine learning approaches [5]. Classical machine learning techniques for stride length estimation are still ongoing research, but they require signal preprocessing and specific feature extraction.…”
Section: Introductionmentioning
confidence: 99%